Enhancing the strength and toughness of WTaTiVN+Taμm heterogeneous alloys via nano Ti–V–N precipitation phase adjustment - Yifei Hu; Ang Xu; Jilong Liu; Ruoqi Wang; Jinping Suo (Journal of Materials Research and Technology)
Addressing the issue of poor toughness due to the intrinsic brittleness of tungsten alloys is critical for their design. In this study, a WTaTiVN system was developed with optimal nitrogen content. By combining nano-sized WTaTiVN powder, micro-sized WTaTiVN powder, and large-grained Ta powder, a high-entropy heterogeneous alloy was obtained with a three-phase structure (WTaTiVN+Taμm) through high-energy ball milling (HEBM) and spark plasma sintering (SPS). This alloy featured dispersed nano Ti–V–N precipitates that formed coherent interfaces, which enhanced strength and toughness through heterogeneous structures and dispersed nanoprecipitates. Mechanical performance tests showed that the three-phase WTaTiVN+Taμm alloy exhibited superior flexural strength and fracture toughness compared to the single-phase WTaTiVN high-entropy alloy and two-phase WTaTiVN+Taμm heterogeneous alloy. Microhardness analysis also indicated heterogeneity in the three-phase WTaTiVN+Taμm alloy. X-ray diffraction (XRD) characterization revealed a heterogeneous BCC polycrystalline structure in the sintered samples. SEM-BSE images and EBSD-IPF maps confirmed the presence of WTaTiVN high-entropy nanocrystalline phases and Ta large-grained crystalline phases. These phases were distributed as islands in the WTaTiVN high-entropy micron crystalline phases. Selected area electron diffraction confirmed the precipitation of the Ti–V–N second phase from the grain boundaries of the WTaTiVN islands and matrix, forming coherent interfaces: (110) HEA//(200) Ti–V–N. The dispersed Ti–V–N precipitates pinned grain boundaries, inhibiting grain growth in the HEA islands and matrix. In addition, they impeded dislocation motion, thereby enhancing strength. By forming coherent interfaces with other parts of the HEA islands and matrix, these precipitates improved the yield strength of the HEA islands and matrix, enhancing material heterogeneity and improving the mechanical properties of the alloy.